(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article examines Academician Buriboy Ahmedov’s research on issues related to the collection, storage, comprehensive study, and publication of rare manuscript works that constitute an important part of scientific and cultural heritage.